Mineralogy and Geochemistry of Upper Cretaceous and Paleogene Succession in Gali and Qalbaza Sections, Northeastern Iraq: Implications for Provenance and Detecting K/Pg Boundary (Iraqi National Journal of Earth Science (INJES), 2026)
One of the most controversial topics in geology is the K/Pg event, marked by mineralogical and geochemical evidence, as well as environmental catastrophes that led to a massive extinction. At the end of the Mesozoic, the Chicxulub meteorite impact and/or prolonged Deccan eruptions were the causes of the global mineralogical and geochemical anomalies at the K/Pg. The Gali and Qalbaza sections in Iraq represent the K/Pg between the upper Tanjero and lower Kolosh formations. The sandstones of these sections are immature lithic graywacke derived from an undissected arc-recycled orogenic provenance, and they were deposited in an arid to semi-arid paleoclimate. REE suggests that a single melt underwent differentiation to provide the source rocks that weathered and were deposited under oxic-anoxic paleoredox conditions. Quartz and K-feldspar increase and carbonate fragments decrease at 10 cm thick of both gray siltstone (sample G19 of Gali section) and red conglomerate layers (sample Q18 of Qalbaza section). The G19 and Q18 layers exhibit low calcite content and the presence of analcime, smectite, and vermiculite. Positive anomalies for SiO2, Al2O3, Fe2O3, MgO, Na2O, K2O, TTEs, Zr, Zn, and Cu, and negative anomalies for CaO, MnO, LOI, Hf, Sr, and Cs are recorded at 10 cm thick G19 and Q18 layers. Elevated levels of Fe/Al, Ni/Al, Cr/Al, and SO2/MnO are also detected at the G19 and Q18 layers. Based on the current evidence, the proposed boundaries of gray siltstone (sample G19) and red conglomerate (sample Q18) layers could represent the K/Pg boundaries, with parts of them perhaps eroded.
Keywords: Geochemistry, Tanjero/Kolosh, K/Pg boundary, Cretaceous, Paleogene